The practice and procedure of the Inter-American Court of Human Rights - Pasqualucci, Jo M. (Cambridge books online., 2003)
Pasqualucci analyzes all aspects of the advisory jurisdiction, contentious jurisdiction, and provisional measures orders of the Inter-American Court of Human Rights, including the Rules of Procedure of the Court and the Commission. This is an important resource for scholars, practitioners, and students of international human rights law and practice.